Biocontrol of Soil Borne Pathogen of Potato Tuber Caused by Rhizoctonia solani through Biosurfactant based Bacillus strain - Hussain, Touseef; Khan, Abrar Ahmad; Khan, M.A. (Journal of Nepal Agricultural Research Council, 2021)
Black scurf disease is a major problem for cultivation of potato worldwide that is managed by synthetic agrochemicals, that are increasing environmental pollution as well as residue in farm produce also. Therefore, now a day use of bio-agents for managing black scurf is attractive feature and need of the hour. A promising bio surfactant OD02 isolate, was isolated from oil contaminated soil, utilizing its secondary metabolite after preliminary biosurfactant screening tests. Furthermore, this strain exhibited positive test with haemolytic activity, emulsification index, oil spreading test, molecular characterization with 16S rRNA universal primers revealed that the strain belongs to Bacillus group, that was further chemically characterized using TLC, exhibiting reddish pink colour as lipopeptide and demonstrated antagonistic activity against Rhizoctonia solani under in vitro using dual culture (45±0.30%) and at 3% concentration under food poisoning method. Bacillus subtilis HussainT-AMU strain is very effective against phytopathogen R. solani and can be more explored in future diseases management strategies.